Digital transformation and organizational restlessness - Besio, Cristina; Jöstingmeier, Marco; Posner, Christine (Frontiers in Sociology, 2024)
In modern society, organizations are expected to be increasingly flexible and adapt to constantly changing environments. While such flexibility is often considered a positive trait of organizations, the risks of continuous organizational change are often overlooked. Against this background, we argue that continuous, multiple and uncoordinated organizational change can lead to a state we define as “organizational restlessness” and a loss of the benefits of stable structures. Paradoxically, it is even possible that organizational restlessness reduces the capability of organizations to planfully introduce specific and highly desirable changes, such as those related to digital transformation. Using qualitative data from interviews and participant observations, we analyze a large German public administration and identify three sources of organizational restlessness: the innovation imperative of modern society, changes in political leadership as a result of democratic elections and the bureaucratic principle of personnel rotation. While barriers to digital transformation are often explained by bureaucratic rigidity, we show that also constant uncoordinated change hinders sustainable digital transformation. Our paper thus contributes to an enhanced understanding of organizational continuity and disruption, as we show that both are needed to digitalize organizations further.